Rural digitization and the urban–rural income gap: a perspective of factor flow - Xiaoai Wen; Yiran Li; Minxi Zhou; Fengcun Feng; Pingping Wang (Frontiers in Sustainable Food Systems)
In recent years, the rapid development of digital technologies and the promotion of rural digitization have profoundly reshaped the development of rural areas and provided new ideas for resolving income disparities between urban and rural residents. This study uses panel data from counties in China between 2018 and 2021 and a two-way fixed effects model to empirically test the impact of rural digitization on the urban–rural income gap and determine the underlying mechanism. The findings suggest that rural digitization effectively reduces the urban–rural income gap, with more pronounced effects in southern regions, eastern regions, central regions, and areas with better agricultural development. Mechanistically, rural digitization narrows the income gap mainly by promoting technological innovation. Rural digitization does not cause more capital to flow into rural areas. Further spatial econometric analysis indicates that the role of rural digitization in narrowing the urban-rural income gap has a significant spatial spillover effect, and this spillover is more likely to occur between counties with similar levels of economic development.